Smoking Cessation Clinic, Hospital’s Participation in Supporting a Quit Smoking Program: A Systematic Review - Rahmah, S; Oktamianti, P (KnE Life Sciences, 2018)
Smoking is a major cause of death worldwide. Analysing smoking cessation clinics as one of the facilities to support the success of smoking cessation in hospitals is the purpose of this systematic review; here will be obtained what methods are used and the effects of these methods in helping smokers quit smoking. This is a systematic review based on PRISMA protocol retrieved from online database such as ProQuest and Emerald. Eight journal articles were chosen as eligible library to be reviewed for qualitative synthesis. Two out of eight articles used counselling therapy as a smoking cessation method, while two other articles used pharmacotherapy, Nicotine Replacement Therapy (NRT), in addition to counselling therapy. Four other articles mention the advantages of having a smoking cessation clinic (SCC) in a hospital. As conclusion, effective counselling can result in behaviour change. The use of NRT combined with counselling can lead to the length of abstinence from smoking. The existence of SCC as an independent unit in the hospital is a strategy to increase the success of smoking cessation. SCC can meet the needs of every patient in their efforts to quit smoking. The suggestion that maintaining continual abstinence should be evaluated and monitored. Keywords: smoking cessation clinic, smoking cessation in hospital, smoking cessation, quit smoking, stop smoking program